Effective nitrogen removal during different periods of a field-scale bioretention system - Wan, Zhexi; Li, Tian; Liu, Yutong (Environmental science and pollution research international, 2018)
Bioretention systems are designed to manage stormwater, but they are always subject to substantial nitrate leaching. In previous laboratory-scale experiments, nitrate removal was enhanced using wood chips as a medium. However, the ability of field-scale systems to transform and remove nitrogen species is not well understood. Here, we report a wood-chip bioretention system that accepts the natural runoff from an elevated highway. The transformation of different nitrogen species indicates that the field-scale system with wood chips also inhibits nitrogen leaching. Nitrate removal was mainly found during the wet period, and was affected by the hydraulic loading rate of the system. Overall, this study showed that the field performance of the wood-chip bioretention system effectively removes nitrogen. In addition, the main period associated with the nitrogen removal process was identified.